2006
DOI: 10.1007/s11524-006-9050-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Asthma and Extreme Values of Body Mass Index: The Harlem Children’s Zone Asthma Initiative

Abstract: To examine the association between body mass index (BMI) percentile and asthma in children 2-11 years of age, we performed a cross-sectional analysis of 853 Black and Hispanic children from a community-based sample of 2-to 11-year olds with measured heights and weights screened for asthma by the Harlem Children's Zone Asthma Initiative. Current asthma was defined as parent/guardian-reported diagnosis of asthma and asthma-related symptoms or emergency care in the previous 12 months. Among girls, asthma prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 34 publications
(45 reference statements)
6
53
2
2
Order By: Relevance
“…In contrast, in the case of the lowest BMI z-score category, the ORs, although not statistically different in this study, appeared elevated in males and reduced in females, which is consistent with the findings of several previous studies that reported low BMI to be associated with asthma particularly in males (4,11,16,17). Furthermore, BF% also demonstrated a consistent U-shape pattern of association with asthma in both preadolescent and adolescent children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, in the case of the lowest BMI z-score category, the ORs, although not statistically different in this study, appeared elevated in males and reduced in females, which is consistent with the findings of several previous studies that reported low BMI to be associated with asthma particularly in males (4,11,16,17). Furthermore, BF% also demonstrated a consistent U-shape pattern of association with asthma in both preadolescent and adolescent children.…”
Section: Discussionsupporting
confidence: 89%
“…The great majority of previous studies on the association of adiposity with asthma in children used BMI as the measure of exposure and focused specifically on the highest range of BMI values (9,30,31). Only a few studies have examined associations across the whole range of BMI values with some of them reporting a linear association of BMI with asthma (1,2,7) while others reporting a U-shape association with an increased risk of asthma in both the underweight and obese groups (15)(16)(17)(18). In our study, the upper range of both measures of adiposity exhibited a positive association with asthma, which in fact appeared stronger in the case of BF% than in the respective BMI z-score category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in adults have shown that obesity and overweight are positively associated with asthma or asthma-like symptoms (1)(2)(3)(4)(5)(6)(7)(8)(9); moreover, in some studies, this association was more pronounced in women than in men (1,(7)(8)(9). In children, on the other hand, results concerning the association of asthma with obesity have not been consistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Data from the National Health and Nutrition Examination Survey showed that a higher body mass index (BMI) was associated with an increased prevalence of asthma among 7505 US children aged 4-17 years (10).…”
Section: Introductionmentioning
confidence: 96%
“…In a cross-sectional study in the United States involving 853 children aged 2-11 years, the prevalence of asthma in association with the *Corresponding author: Keiko Tanaka, D.D.S., Ph.D., Department of Preventive Medicine and Public Health, Faculty of Medicine, Fukuoka University, 7-45-1, Nanakuma, Jonan-ku, Fukuoka 814-0180, Japan; Tel: +81 92 801 1011 extn. 3315; Fax: +81 92 863 8892; E-mail: k-tanaka@fukuoka-u.ac.jp BMI percentile in boys followed a U-shaped curve, whereas the prevalence of asthma increased linearly with higher BMI percentiles in girls (12).…”
Section: Introductionmentioning
confidence: 99%